Factors influencing health-related quality of life in older adult women with sarcopenia: analysis of the Korean National Health and Nutrition Examination Survey 2019 - Sol Hyun Lee; Ju-Hee Nho; Hye Young Kim; Eun Jee Lee (Korean Society of Women Health Nursing, 2023)
Purpose This study aimed to identify factors influencing the health-related quality of life (HRQoL) of older adult women with sarcopenia. Methods The study was secondary data analysis using data from the 2019 Korea National Health and Nutrition Examination Survey. The final sample consisted of 142 women aged 60 years and older with sarcopenia and were selected from 8,110 women. The participants was analyzed using complex descriptive statistics, independent t-test, and regression. Results In terms of HRQoL, three general characteristics were found to be influential, with an explanatory power of 56.0%: difficulty climbing stairs, difficulty working, and perceived health status. Having no or mild difficulty when climbing stairs (B=.20, p=.001; B=.21, p<.001) and no or mild difficulty when working (B=.25, p=.002; B=.208, p=.013) had a significant effect on HRQoL compared to severe difficulty. Having good or ordinary perceived health status had a significant effect on the HRQoL (B=.11, p<.001; B=.09, p<.001). Conclusion Based on study findings that the HRQoL of older adult women with sarcopenia were influenced by difficulty climbing stairs and working, as well as good perceived health status, healthcare providers should assist elderly women to maintain physical activities in their daily lives.